Nitrogen and Sulfur Dual-Doped Carbon Microtubes with Enhanced Performances for Oxygen Reduction Reaction. Issue 5 (18th February 2016) - Deng, Libo; Fang, Haoming; Zhang, Peixin; Abdelkader, Amr; Ren, Xiangzhong; Li, Yongliang; Xie, Ning
Abstract : Porous carbon microtubes were prepared by pyrolysing an inexpensive and abundant natural fungus at a high temperature, followed by activation and doping with nitrogen (N) and sulfur (S) elements at a lower temperature. The performance of the porous carbon as electrocatalysts for oxygen reduction reaction (ORR) was systematically investigated. The pristine carbon without doping shows a high electrocatalytic activity, which is strongly dependent on the degree of graphitization. By N- and S- dual-doping, the catalytic performance is further enhanced, exhibiting a four-electron oxygen reduction pathway, which is attributed to the redistribution of spin and charge densities. These results suggest that obtaining graphitic porous carbon from natural precursors combined with heteroatom-doping, provide an effective method of producing high performance carbon materials which might be suitable for various electrochemical energy applications.